Vitrification Ovulate: A Inteligent Decision. Role Of The Psychologist In The Treatment Assisted Reproduction - Cases Jiménez, Gabriela (2015)
A literature study with the main objective to analyze the vitrification ovulate(egg freezing) as one of the techniques of assisted reproduction and clarify the role of Psychologists in these processes was performed. Analysis of the ovular vitrification was aimed at determining the characteristics and comparative advantages, to raise it as a (maternity insurance) “wise decision” and review the current status of vitrification ovulate and future prospects. The issue referred to the role of the Psychologist in assisted human reproduction examined the emotional impact that infertility spouses, the actions you can take the psychologist in this field, the need for specific academic training required professional psychologist in this field, the assessment tools are there, and finally the attitudes and values that the psychologist should be displayed in this context. The findings emphasized the importance and desirability of vitrificationovulate as assisted reproductive technology and the need